Pengaruh Perhatian Orang Tua, Fasilitas, Dan Motivasi Belajar Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial (IPS) - Ari Ratna Juwita (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
The role of parents, learning facilities and learning motivation are factors that can affect learning achievement. This study aims to determine whether parental attention, learning facilities, and learning motivation affect children's learning achievement. This type of research is a non-experimental quantitative research (ex post facto) with a survey approach. The population of this study were all students. With a research sample of 55 students. The instrument used is a questionnaire. The data analysis technique used statistical t and F tests. The results of hypothesis testing showed; 1) there is a simultaneous influence between parental attention, learning facilities and learning motivation in learning achievement with a significant value of 0.026 < 0.05 (p < 0.05); 2) there is an effect of parental attention on learning achievement with a significant value of 0.000 < 0.05 (p < 0.05) or 76.8%; 3) there is an effect of learning facilities on learning achievement with a significant value of 0.000 < 0.05 (p < 0.05) or 75.28%; 4) there is an effect of learning motivation on learning achievement with a significant value of 0.000 < 0.05 (p < 0.05) or 77.16%. The conclusion in this study is that parents' attention, learning facilities and learning motivation must continue to be obtained by children so that their learning achievements will be better in the future.